Epilepsy and ADHD - Giffoni, Silvyo David Araújo (2012)
Epilepsy and ADHD are common neuropsychiatric disorders in childhood and adolescence. ADHD affects approximately 3-7% of school-aged children and the prevalence of epilepsy is 1.5 to 8.9 / 1,000 children and adolescents. Both disorders interfere in academic and social functioning. A review was carried out of the literature from the last 10 years in MEDLINE and LILACS with the combination of the keywords “ADHD” and *Epilepsy”. The purpose of this review was to search the literature for data that could explain the association between the two diseases and the best form of treatment of that association.